Dental management of a 3-year-old uncooperative child under general anaesthesia: a case report - Joshi, Ambika; Saxena, Nivedita; Marwah, Nikhil; Singh, Vritika; Singh, Mrityunjay (International Journal of Contemporary Pediatrics, 2023)
Dental care is medically necessary for the purpose of eliminating and preventing orofacial disease, infection and pain, restoring the form and function of the dentition, and correcting facial disfiguration or dysfunction – American Academy of Pediatric Dentistry (AAPD). Lack of cooperation in young paediatric patients can be a confounding factor for dental rehabilitation procedures and even examination or radiographs. To complete necessary dental radiographs and/or treatment in young, uncooperative children general anaesthesia or deep sedation is often required. This article presents the case of a 3-year-old girl child with a complaint of sharp shooting pain in upper and lower left back tooth region and was extremely uncooperative. She was diagnosed with early childhood caries; full mouth rehabilitation was done under general anaesthesia. Clinical examination, classification and treatment plan are discussed based on the review of current literature available.